Translating traditional Malay pottery motifs to inspire ceramic surface decoration design / Siti Maryam Ali Yasin ... [et al.] - Ali Yasin, Siti Maryam; Haron, Hamdzun; Ramli, Zuliskandar; Tular, Suhaimi; Mohd Raffie, Mohd Shahrol Hanafi (Universiti Teknologi MARA, Perak, 2021)
A particular ceramic product offered by the designers and manufacturers is measured based on its appearance and performance from aesthetic value, design and craftsmanship quality. Products in our daily life play an essential role in bringing us happiness, comfort, convenience and satisfaction to the consumers and buyers. In a Malay community in Malaysia, the Malay Traditional Pottery is one of the Malay arts heritages. Its products used to have a high demand among the locals as well as people from abroad. However, today, demand for Malay Traditional Pottery from the locals has declined significantly. Hence, to improve the product appearance, this study highlights one of the essential factors in ceramic design features, namely surface decoration, by using motifs derived from the Malay Traditional Pottery onto the new contemporary design of the local ceramic products. The surface decoration consists of motifs, patterns, colours, techniques and materials. Surface decoration study would give designers and local ceramic entrepreneurs the product appearance improvement. With such improvements, local ceramic products would become a preferred choice for the consumer’s daily use. This study also aimed to entice the designer to be involved in pattern design and ceramic product surfaces.